Practical guidance for healthcare professionals during the COVID-19 pandemic; with special emphasis on the care of cardiovascular patients and personal protection - Chugh, Yashasvi; Chugh, Sunita; Chugh, Sanjay (International Journal of Medical Research and Review, 2020)
A novel, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is causing the COVID-19 pandemic. There are concerns regarding the spread of disease by asymptomatic carriers to healthcare workers who continue to see patients and to perform procedures on them. The infection then could be transmitted through them to other patients who eventually, could infect persons in the community. Further, limitations of existing tests to detect new cases that are negative early in the disease; and the inability to use appropriate personal protection equipment (PPE)also contribute to the spread of infection. This document, from the COVID-19 Working Group of Wellness and Radial Intervention Society, describes considerations for management and care of cardiovascular disease (CVD) patients with the concept of COVID 19 `designated` Vs. enabled` centers for those with symptoms of and/ or confirmed COVID-19 disease Vs. asymptomatic suspects. It also provides guidance to healthcare professionals, hospital administrators, and policymakers in general and to those managing patients with CV and other diseases, regarding the concept of `levels of personal protection` for staff; with suggestions for `equivalent innovative alternatives`, and a` protection plan` for patients to prevent the spread of disease. The guidance can also be broadly applied to surgical branches in general and to other specialties involved with invasive, semi-invasive, and non-invasive procedures such as gastroenterology, urology, anesthesiology, otolaryngology, and ophthalmology which carry a higher risk of exposure for healthcare professionals.